Effect of compounds on the purification and antibody preparation of the extracellular domain fragment of the receptor CD163 - Qi Wen-Bao; Jiao Pei-Rong; Guo Si-Hu; Yan Ming-Fei; Sun Wei-Wei; Jia Kun; Zhao Fu-Rong; Cao Zong-Xi; Zhang Gui-Hong (Virology Journal, 2011)
Abstract Background Porcine reproductive and respiratory syndrome virus (PRRSV) has been acknowledged as one of the most important agents affecting swine. The scavenger receptor CD163 is one of the important entry mediators for PRRSV. Results The tD4 and tD5 CD163 genes were amplified, and the PCR products were cloned into pET-28a(+) (designated pET-28a-tD4 and pET-28a-tD5, respectively). The plasmids pET-28a-tD4 and pET-28a-tD5 were then transformed into the E. coli BL21 (DE3) strain and expressed by adding 1 mmol/L of isopropyl-beta-D-thiogalactopyranoside. The proteins were highly expressed in the supernatant from the tD4- and tD5-producing cells that were incubated with a binding buffer containing the following compounds: β-mercaptoethanol, urea, Tween 20, glycerol, and SDS, while they were rarely expressed in the supernatant from the tD4- and tD5-producing cells that were incubated with binding buffer without the compounds. The tD4 and tD5 proteins were purified, and BALB/c mice were immunized with the purified proteins. Western blotting analysis showed that the tD4 and tD5 proteins were capable of reacting with tD5 antibodies; the titer of both the tD4 and tD5 antiserums was 1:160 against the tD5 protein, as shown by ELISA. Conclusions These studies provide a new way for the purification of proteins expressed in inclusion bodies and the preparation of the corresponding antibodies.